1984
DOI: 10.1007/bf02555524
|View full text |Cite
|
Sign up to set email alerts
|

Isolated ischemic necrosis of the cecum in patients with chronic heart disease

Abstract: Isolated ischemic necrosis of the cecum is an infrequently described entity. We report three cases seen at our institution within a three-year period. All three patients had been hospitalized for congestive heart failure in the past, but none was in failure at the time of the most recent hospitalization. All three patients presented with clinical and laboratory findings consistent with acute appendicitis. At surgery the cecum was ischemic in each case, while the appendix and the remainder of the intestine appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 10 publications
0
27
0
4
Order By: Relevance
“…This proximal predilection in low fl ow states such as shock can be attributed to vasospastic refl ex, shunting, and the cecum's blood supply from end arteries and an inconstant arcade. [16] Although "runner's diarrhea" is common among marathon participants, the presence of bloody bowel movements after an endurance event should raise the possibility of ischemic colitis. [1,9] History questions regarding risk factors for ischemia such as personal or family history of hypercoagulability, medication history, risk factors for hypovolemia (environmental conditions (heat), amount of fluid ingested) should all be posed.…”
Section: Discussionmentioning
confidence: 99%
“…This proximal predilection in low fl ow states such as shock can be attributed to vasospastic refl ex, shunting, and the cecum's blood supply from end arteries and an inconstant arcade. [16] Although "runner's diarrhea" is common among marathon participants, the presence of bloody bowel movements after an endurance event should raise the possibility of ischemic colitis. [1,9] History questions regarding risk factors for ischemia such as personal or family history of hypercoagulability, medication history, risk factors for hypovolemia (environmental conditions (heat), amount of fluid ingested) should all be posed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described in association with vascular occlusive disease and with low flow states. Rist et al [ 1 ] reported isolated ischaemic necrosis of the caecum in 3 patients with chronic heart disease. All 3 patients presented with clinical findings consistent with acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed by Rist et al that the cecum is a ''watershed area,'' with a blood supply that is poorer than the adjacent intestine similar to the splenic flexure and rectosigmoid colon. 24 The cecum is supplied by end arteries from the anterior and posterior cecal arteries, which are terminal branches of inferior branch of the ileocolic artery. Indeed, a period of hypotension may have contributed to this case of spontaneous cecal perforation, although there was no evidence in this case.…”
Section: -11mentioning
confidence: 99%